Students’ perception to increase students' engagement in learning project management - Nasrudin Mohammed, Nor Syamaliah Ngah, Thenmolli Vadeveloo, Norazlin Abd Aziz, (Opción, 2019)
This study explores the behavioural intention to use the new holistic technical module by looking at the factors of perceived ease of handling and recognising useful utilization of the module. A cross-sectional research is used by distributing a set of questionnaires to students at University Technology MARA. The results suggest that the lecturers should play their role to increase the students’ perceptions towards the usefulness that will contribute to the implementation of the module and its success. In conclusion, educators must look at this factor whenever they want to innovate any form of support material in teaching and learning.